2014
DOI: 10.1590/bjft.2014.014
|View full text |Cite
|
Sign up to set email alerts
|

Perfil socioeconômico e profissional de manipuladores de alimentos e o impacto positivo de um curso de capacitação em Boas Práticas de Fabricação

Abstract: Doenças transmitidas por alimentos constituem um problema de saúde pública em nível mundial e estão frequentemente associadas a falhas na manipulação dos alimentos. Conhecer o perfil socioeconômico e profissional, bem como o nível de conhecimento dos manipuladores de alimentos, é requisito essencial para o planejamento de políticas públicas e programas de capacitação visando a segurança e qualidade dos alimentos. Este trabalho teve por objetivo avaliar o perfil socioeconômico e profissional de manipuladores de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
25

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 7 publications
(7 reference statements)
1
10
0
25
Order By: Relevance
“…In a study by Devides, Maffei, and Catanozi (2014), when questioned why they sought training courses in good handling practices, the participants reported that it was because of the requirements of the sanitary inspection agency, which indicates the importance of the actions of these agencies, whose main purpose is to guide, monitor, and licensing the establishments to handling, produce, market, distribute, and/or store food (Harris, Dipietro, Murphy, & Rivera, 2014;Läikkö-Roto, Makela, Lundén, Heikkila, & Nevas, 2015).…”
Section: % Adequacymentioning
confidence: 99%
“…In a study by Devides, Maffei, and Catanozi (2014), when questioned why they sought training courses in good handling practices, the participants reported that it was because of the requirements of the sanitary inspection agency, which indicates the importance of the actions of these agencies, whose main purpose is to guide, monitor, and licensing the establishments to handling, produce, market, distribute, and/or store food (Harris, Dipietro, Murphy, & Rivera, 2014;Läikkö-Roto, Makela, Lundén, Heikkila, & Nevas, 2015).…”
Section: % Adequacymentioning
confidence: 99%
“…O período de exposição do alimento no buffet acarreta muitas vezes perdas de temperatura (Tabela 3). Esta intercorrência pode ser observada mesmo quando as temperaturas iniciais (saída da cozinha central) estavam acima de 60°C, enquanto nas finais (10 minutos antes do início da distribuição) apresentavam-se abaixo do recomendado [6,20].…”
Section: Resultsunclassified
“…All food producing places must follow the minimum requirements, based on good manufacturing practices to ensure the quality of the food produced, and to ensure this quality, the handlers present themselves as the main factor that must be qualified and be aware of the associated risks to their activity, since in many places of food manufacturing it is observed the ignorance of the manipulators on the appropriate conduits for manipulation (Devides et al, 2014).…”
Section: Concept and Regulation Of Good Manufacturing Practicesmentioning
confidence: 99%